Science-Policy Dialogue on Strengthening Climate Adaptation Strategies Towards Climate Resilience in Senegal: Insights from National Stakeholder's Workshop - Akinseye, Folorunso M.; Govind, Ajit; Gueye, Cheikh; Kumar, Shalander; Ouédraogo, Issa; Worou, Nadine (CGIAR System Organization, 2023)
The CGIAR Research Initiative on Climate Resilience (ClimBeR) is one of the CGIAR Research Initiatives that aims to improve the adaptation capacity of food, land, and water systems to climate change in six countries, including Senegal. As part of this initiative, a two-day science-policy dialogue addressed various aspects of the food system’s sustainability in Senegal, highlighting specific vulnerabilities, initiatives, challenges, and potential solutions. To sum up, the insights distilled from these policy dialogues underscore crucial aspects and potential pathways for improvement, emphasizing the imperative of collaborative efforts to enhance climate resilience in Senegal.